Richard II - William Shakespeare; Lothian, John M. (1955)
The Old Vic Theatre, Old Vic Trust Ltd. in association with The Arts Council of Great Britain presents The Old Vic Company in the plays of Shakespeare, director Michael Benthall, administrative director Alfred Francis, "Richard II," by William Shakespeare, produced by Michael Benthall, decor and costumes by Leslie Hurry, music composed by Christopher Whelen..
The Old Vic Theatre, 1955.
"1954/1955 season. The Old Vic Company. Richard II. William Shakespeare"--Cover.
Title devised by Library staff.
Cast: John Neville, Meredith Edwards, Eric Porter, Robert Hardy, Mary Hignett, Charles Gray, Anthony White, Robin Barbary, Arthur Blake, Murray Hayne, John Wood, Nicholas AMer, Michael Bates, Virginia McKenna, Laurence Hardy, Ronald Fraser, Geoffrey Chater, Brian Rawlinson, Alan Dobie, Christopher Burgess, Raymond Llewellyn, John Woodvine, Donald Moffat, Jane Jacobs, Anne Robson, Loretta Davett, Job Stewart, Aubrey Morris, Kerrigan Prescott, Clifford Williams, Robert Gillespie, Murray Hayne.
LC copy has notations by Coe.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: English drama; Theater programs -- England -- London; Theater programs -- 1955.